Legal Analysis of the Termination of a Fixed-Term Employment Agreement Based on a Court Decision No: 50/Pdt.Sus-PHI/2025/PN.Mdn - Elfhadjri, Ziqra; Nasution, Abdul Razak; Rafianti, Fitri (JURNAL HUKUM SEHASEN, 2026)
This study examines fixed-term employment agreements (PKWT) as a form of employment relationship with a limited duration, but often raises legal issues when termination of employment occurs that does not comply with statutory provisions. These issues usually arise from differences of opinion regarding the terms, procedures, and legal protections for workers and employers. This study uses a normative juridical method with a statutory approach and case studies of court decisions. The analysis of Decision Number: 50/Pdt.Sus-PHI/2025/PN.Mdn shows that courts generally emphasize compliance with Law Number 13 of 2003 concerning Manpower, as amended by Law Number 6 of 2023 concerning the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation, in assessing the validity of termination of employment in PKWT. Court decisions also demonstrate efforts to balance the interests of employers with the protection of workers' rights, particularly regarding compensation, damages, and legal certainty. Thus, it can be concluded that the role of the court is very important in providing justice and legal certainty for the parties in employment disputes, while also strengthening the implementation of employment regulations.